Global research trends on bacterial contamination and microbiological quality of ready-to-eat foods: a bibliometric analysis - Abubaker, Kawooya; Eilu, Emmanuel; Akinola, Saheed Adekunle; Kafeero, Hussein Mukasa; Danladi, Makeri; Adebayo, Ismail Abiola; Nakavuma, Jesca (Frontiers in Research Metrics and Analytics, 2026)
BackgroundReady-to-eat (RTE) foods are increasingly consumed worldwide due to urbanization, dietary shifts, and globalization of food systems, yet they remain a significant vehicle for foodborne diseases. Despite the growing body of research, a systematic mapping of global scientific trends in this area has been lacking.MethodsWe conducted a bibliometric analysis of RTE food microbiology research indexed in Scopus from 1973 to 2025. Publication trends, citation patterns, leading authors, institutions, journals, and country-level contributions were assessed using Bibliometrix. Network analyses (co-authorship, bibliographic coupling, and keyword co-occurrence) were performed using VOSviewer to identify collaborative structures and thematic evolution.ResultsA total of 780 publications across 256 sources were identified, growing at an average annual rate of 6.9%. The field accumulated 19,811 citations, with highly cited works between 1996 and 2015 establishing its intellectual foundations. China, Italy, and the USA led in productivity, while Public Health England, Universidad de Córdoba, and China's Institute of Microbiology were major institutional hubs. Journal of Food Protection, International Journal of Food Microbiology, and Food Control dominated as key sources. Collaboration networks revealed strong international linkages, particularly among high-income countries. Keyword analysis showed two thematic axes: persistent focus on classical pathogens (Listeria monocytogenes, Salmonella, Bacillus cereus) and emerging concerns related to convenience foods, and fast foods.ConclusionResearch on the microbiological safety of RTE foods has grown steadily, reflecting global recognition of its public health significance. However, outputs remain concentrated in high-income countries, while low- and middle-income regions with high foodborne disease burdens are underrepresented. Future research should prioritize equitable global participation, integration of genomic and omics tools, and translation of findings into food safety policy. This bibliometric evidence highlights the need for stronger international collaboration to ensure the microbiological safety of RTE foods in an era of rapid dietary transition.